ANALISIS PENGARUH IKLAN, HARGA DAN KUALITAS PRODUK TERHADAP PURCHASE DECISION PRODUK SKINCARE MS GLOW DI PURWOKERTO - Meydy Fauziridwan (Journal of Data Science Theory and Application, 2022)
Lately, there are many new skincare products circulating in Indonesia. This is due to the availability of opportunities to gain market share in the skincare product business sector in Indonesia. The purpose of this study is to determine the effect of the dimensions of Advertise, Price and Product Quality on Purchasing Decisions for MS Glow products.This research is a quantitative research and the respondents in this study were 111 respondents. In this study the sample was taken by non-probability sampling, namely the accidental sampling technique. Based on the data analysis shows that: (1) Advertise has a positive and significant effect on Purchase Decisions, (2) Price has a positive and significant effect on Purchase Decisions, (3) Product Quality has a positive and significant effect on Purchasing Decisions